Effects of injection strategy and coolant temperature on hydrocarbon and particulate emissions from a gasoline direct injection engine with high pressure injection up to 50 MPa. (1st December 2018) - Song, Jingeun; Lee, Ziyoung; Song, Jaecheon; Park, Sungwook
Abstract: The present study investigated the effect of coolant temperature, injection pressure, and injection timing on emissions in a gasoline direct injection (GDI) engine. Two coolant temperatures of 40 °C and 80 °C, and wide range of injection timings from before top dead center (BTDC) 360° to BTDC 210° were tested under injection pressures in the range of 5 MPa–50 MPa. Particle number (PN), soot, total hydrocarbon (THC), and nitrogen oxides (NOx) were measured under the various experimental conditions. In addition, the spray and flame images were used to observe the spray-wall interaction and to identify the existence of a fuel film. Experimental results showed that the increase in injection pressure significantly reduced the particulate emissions, especially for the wall wetting condition (BTDC 330°). The PN emissions from the wall wetting condition was reduced by about 90% by increasing injection pressure from 10 MPa to 50 MPa. Furthermore, increasing the coolant temperature was an effective way to reduce the PN, soot, and THC. In particular, the THC was reduced by about 30%, while the change in injection pressure and injection timing varied by only 10%. Highlights: Effects of high injection pressure (up to 50 MPa) and coolant temperature on PN emissions were analyzed. We achieved 90% reduction in PN emissions by applying 50 MPa injection pressure from 10 MPa. Increased coolant temperature contributed to decrease PN, soot, and THC emissions.